2017
DOI: 10.1159/000455823
|View full text |Cite
|
Sign up to set email alerts
|

Primary Prevention Strategies for Anthracycline Cardiotoxicity: A Brief Overview

Abstract: The clinical use of doxorubicin and other antitumor anthracyclines is limited by a dose-related risk of cardiomyopathy and heart failure which may occur “on treatment” or any time, from months to years, after completing chemotherapy. Dose reductions diminish the incidence of cardiac events attributable to anthracyclines, but heart failure still occurs in some patients exposed to low or moderate anthracycline doses. Because anthracyclines improve the life expectancy of patients with, for example, breast cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 61 publications
0
53
0
1
Order By: Relevance
“…Although various cancer immunotherapies have emerged (Wang, 2017), chemotherapy remains one of the most effective treatments for advanced cancers (Benevento et al, 2017;Menna and Salvatorelli, 2017). However, chemotherapeutic drugs usually cause immunosuppression, which impairs their antitumor effects.…”
Section: Discussionmentioning
confidence: 99%
“…Although various cancer immunotherapies have emerged (Wang, 2017), chemotherapy remains one of the most effective treatments for advanced cancers (Benevento et al, 2017;Menna and Salvatorelli, 2017). However, chemotherapeutic drugs usually cause immunosuppression, which impairs their antitumor effects.…”
Section: Discussionmentioning
confidence: 99%
“…Anthracyclines, including doxorubicin, epirubicin, daunourubicin, and idarubicin, play a major role in chemotherapy and are used to treat many solid organ tumours and haematologic malignancies such as breast, ovarian, lung, uterine, and bladder cancers, and different types of leukaemias and lymphomas [28,29]. However, it is widely reported that dose-dependent cardiotoxicity of anthracyclines limit their clinical effectiveness [1-4, 28, 29].…”
Section: Discussionmentioning
confidence: 99%
“…Cardioprotective Agents Against Anthracycline -Induced Cardiotoxicity: Drugs used clinically for prevention of anthracycline (doxorubicin) induced toxicity are shown in Table 2. Unfortunately, none of the drugs till date is clinically established as a cardioprotective agent against anthracycline (doxorubicin -induced toxicity) 22 .…”
Section: 2mentioning
confidence: 99%